1995
DOI: 10.1021/tx00047a019
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Glutathione Conjugation in Vitro by 1H NMR Spectroscopy. Uncatalyzed and Glutathione Transferase-Catalyzed Reactions

Abstract: Conjugation reactions of glutathione (GSH) and related thiols with diethyl maleate (DEM) and other alpha, beta-unsaturated carbonyl compounds have been investigated by 1H NMR spectroscopy. The products from the reaction with DEM and diethyl fumarate (DEF) are shown to be the diastereomers of S-(alpha,beta-diethoxycarbonylethyl)glutathione. During the course of the reaction, DEM isomerized to DEF, and the rate of isomerization was dependent upon whether the solvent was 1H2O or 2H2O. The observed rate data exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…Previous reports have demonstrated that DEM treatment increases the relative GSSG levels of cells (55,60,61), and our results show that DEM treatment of 3T3 cells leads to inactivation of GABP DNA binding activity, possibly by direct oxidation by GSSG. To test the ability of GSSG to directly oxidize GABP and thereby inhibit its DNA binding activity, 3T3 cell nuclear extracts were treated with DTT, GSSG, or GSH, and the effect on GABP dimer and tetramer DNA binding activities was determined by EMSA analysis using the dPEA3-0 probe (Fig.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Previous reports have demonstrated that DEM treatment increases the relative GSSG levels of cells (55,60,61), and our results show that DEM treatment of 3T3 cells leads to inactivation of GABP DNA binding activity, possibly by direct oxidation by GSSG. To test the ability of GSSG to directly oxidize GABP and thereby inhibit its DNA binding activity, 3T3 cell nuclear extracts were treated with DTT, GSSG, or GSH, and the effect on GABP dimer and tetramer DNA binding activities was determined by EMSA analysis using the dPEA3-0 probe (Fig.…”
Section: Resultssupporting
confidence: 76%
“…NAC may protect cells from the action of DEM by direct chemical conjugation with DEM, by antioxidant action, or by replenishing GSH levels through biosynthesis of GSH from NAC, its immediate biosynthetic precursor (55). Chemical (nonenzymatic) reaction of NAC with DEM is relatively slow (Ͻ20% after 1 h), whereas enzymatically catalyzed DEM depletion of GSH in cultured cells is nearly 80% complete in Ͻ1 h (60,61). Under the conditions of our experiments, only a small fraction of the DEM would likely be lost to direct chemical conjugation with NAC, suggesting that the protective effect of NAC on DEM inhibition of GABP DNA binding is the restoration of GSH levels.…”
Section: Discussionmentioning
confidence: 99%
“…DEM (32,33) is a commonly used agent for acute GSH depletion because it diffuses freely into cells due to its hydrophobicity and forms glutathione conjugates in reactions catalyzed by glutathione S-transferase (Fig. 3A).…”
Section: Promoter Forward (F) and Reverse (R) Primers And Taqman Probmentioning
confidence: 99%
“…Diethyl maleate binds irreversibly to glutathione and is frequently used to deplete intracellular glutathione (Boyland & Chasseaud, 1967;Kubal et al, 1995). In these studies, diethyl maleate caused a signi®cant depletion of hepatic (14.6+9.6% of control levels; P50.05) and extrahepatic [PBMC (55.0+22.2% of control levels; P50.05); splenocytes (51.4+17.6% of control levels; P50.05)] glutathione.…”
mentioning
confidence: 99%